First asymmetric synthesis of the Kelatorphan-like enkephalinase inhibitor (1S,2R,2 ' S)-2-[2 '-(N-hydroxycarbamoylmethyl)-3 '-phenylpropionylamino]cyclohexane-1-carboxylic acid - Davies, S; Dixon, D (1998)
The first asymmetric synthesis of Kelatorphan-like enkephalinase inhibitor (1S,2R,2′S)-2-[2′-(N-hydroxycarbamoylmethyl)-3′- phenylpropionylamino]cyclohexane-1-carboxylic acid is achieved using lithium amide (R)-5 and pyrrolidinone auxiliary (R)-6; the pyrrolidinone auxiliary is used to create (2S)-benzylsuccinic acid derivative (S)-4 while lithium amide (R)-5 is used to synthesize tert-butyl (1S,2R)-2-aminocyclohexanecarboxylate 3.